2018
DOI: 10.1016/j.funeco.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Coming up short: Identifying substrate and geographic biases in fungal sequence databases

Abstract: Insufficient reference database coverage is a widely recognized limitation of molecular ecology approaches which are reliant on database matches for assignment of function or identity. Here, we use data from 65 amplicon high-throughput sequencing (HTS) datasets targeting the internal transcribed spacer (ITS) region of fungal rDNA to identify substrates and geographic areas whose underrepresentation in the available reference databases could have meaningful impact on our ability to draw ecological conclusions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Compared to other terrestrial habitats, fewer genomic studies have been conducted in aquatic habitats. As a result, fewer ITS sequence records are available and new phylogenetic groups are expected to be found (Grossart et al 2019;Khomich et al 2018). Furthermore, for basal fungi living in an aquatic habitat, such as chytrids, more conservative regions such as large subunit (LSU) and small subunit (SSU) regions of rDNA are often used (Nilsson et al 2019).…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Compared to other terrestrial habitats, fewer genomic studies have been conducted in aquatic habitats. As a result, fewer ITS sequence records are available and new phylogenetic groups are expected to be found (Grossart et al 2019;Khomich et al 2018). Furthermore, for basal fungi living in an aquatic habitat, such as chytrids, more conservative regions such as large subunit (LSU) and small subunit (SSU) regions of rDNA are often used (Nilsson et al 2019).…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Compared to other terrestrial habitats, fewer genomic studies have been conducted in aquatic habitats. As a result, fewer ITS sequence records are available and new phylogenetic groups are expected to be found (Grossart et al, 2019; Khomich et al, 2018). Furthermore, for basal fungi living in an aquatic habitat, such as cystrids, more conservative regions such as large subunit (LSU) and small subunit (SSU) regions of rDNA are often used (Nilsson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, approximately 40% of all OTUs could not be identified, which could be partly due to differences in barcoding regions, especially in the ancestral lineages. In addition, the environmental sequences often return unknown lineages of fungi, and some of the OTUs for which taxonomic and functional groups could not be estimated in the present study may be due in part to insufficient DNA and functional data in the database (Grossart et al, 2019;Khomich et al, 2018). Recently, long-read sequencing technology (e.g., Oxford Nanopore) has been used to decipher the SSU-ITS-LSU region to infer the phylogenetic position of OTUs with no closely related sequences registered in the database (e.g., Tedersoo et al, 2020).…”
Section: Technical Challengesmentioning
confidence: 92%